Development of an Optimization Algorithm for Internet Data Traffic - Misbahuddin, Syed (2020)
In recent era of Information Technology the data traffic over the Internet is increasing uncontrollably. This proliferation of data traffic is due to general shift towards e-business and other application of Information Technology. The businesses relying on Internet lose billions of dollars each year due to slow or failed web services. Therefore, in Internet research, the most conspicuous issue is to develop methodologies to reduce net traffic over the Internet. In this paper, an optimization algorithm is proposed to reduce net data traffic, which works at Internet layer in the TCP/IP reference model. The algorithm monitors data repetitions in IP datagram and prepares a compression code in response of this repetition. If no IP datagrams are repeated, no compression code is sent. Therefore, the algorithm does not put any overhead on the system. Furthermore, as the proposed algorithm works at IP datagrams only, therefore, it remains transparent from all client-server applications.